ANALISIS KONDISI KESULITAN KEUANGAN PERUSAHAAN MENGGUNAKAN MODEL ALTMAN MODIFIKASI (Z-SCORE), ZAVGREN (LOGIT), SPRINGATE (S-SCORE) DAN ZMIJEWSKI (X-SCORE) (STUDI PADA PERUSAHAAN RITEL YANG LISTING DI BEI) - Khairi, Awalul (journal of RESIDU, 2018)
Financial report can be used to predict the future of a company.meanwhile, management use it to anticipate future condition and more importantlyas start up to make action plan to predit the future. Main objective of this research is to predict financial distress condition listed at Indonesian Stock Exchange (IDX) period 2010-2014 according to Model Altmant Modification (Z”-score), Zavgren (Logit), Springate (S-Score) dan Zmijewski. This research using secondary data from financial report of ritel company according to classification of Indonesian Capital Market Directory listed at Indonesian Stock Exchange since 2010 until 2014. Data from publication of Indonesia Stock Exchange. Analysist result shows that Zavgren model have more accurate than three others models that is Altman modifcations, Springate and Zmijewski to predict bankruptcy. The main factor is Altman Modification model take more variable ahead than three others. Keywords: financial distress, financial report, condition of the company.